Comparative analysis of the lethality pattern of Covid-19 and the response of BRICS countries to the pandemic in the context of multilateralism: An ecological study - Thalyta Cássia de Freitas Martins; Adelyne Maria Mendes Pereira; Cristiani Vieira Machado; Carlos Machado de Freitas; Raphael Mendonça Guimarães (PLoS ONE, 2025)
Background This article analyzes the pattern of lethality due to Covid-19 in the BRICS countries and its conditioning factors, analyzing its temporal evolution, as well as analyzing the response given by the grouping to the health crisis as a multilateral forum. Methods This ecological time-series study assessed the lethality due to Covid-19 in the BRICS countries from March 2020 to May 2023. Using the Joinpoint method, and the temporal trend analysis of the lethality rates by segmented regression for each BRICS country. Results In Brazil, the highest case fatality rate (8%) occurred in phase 1 (from April 27, 2020 to November 10, 2020), despite the peak in cases (1.2 million/week) in phase 3 (from December 31, 2021 to April 21, 2022). In Russia, phase 2 (from September 20, 2020 to March 7, 2021), which had the lowest incidence, had the second highest case fatality rate (4.5%). In India, the peak in cases in phase 2 (from March 13, 2021 to July 19, 2021) did not coincide with the peak in case fatality in the same phase. In China, the highest case fatality rate (12%) occurred in phase 1 (from March 10, 2022 to March 24, 2022), not reflecting the incidence. In South Africa, at the end of 2022, the fatality rate achieved was around 4.5%. Discussion The lethality of Covid-19 among BRICS countries showed differences related to failures in testing capacity, death information systems and access to vaccines. The group did not achieve the expected performance at an extremely opportune moment to demonstrate to the world their differential as representatives of emerging powers.